Entwicklungstendenzen germanistischer Studiengänge im Ausland Sprache, Philologie, Berufsbezug - Middeke, Annegret (Universitätsverlag Göttingen, 2010)
21 articles give insights into German Studies outside the German-speaking countries. The contributions cover as wide a range as reports country by country, descriptions of individual profiles and local study plans, conceptual cross-country approaches and analyses of specific aspects of general relevance. In all their diversity, the articles demonstrate, besides the basic consensus that German and Germany are to be taught as manifestations of another culture, further similarities: Almost without exception German studies have entered a transitional phase that is not only characterized by curriculum reforms but also by discussions about the identity of German studies themselves. Here, the practical orientation seems to be a central point since, more and more, German Studies are seen as a professional education, too.